HUBUNGAN STUNTING DENGAN PERKEMBANGAN MOTORIK HALUS PADA BALITA USIA 24 – 59 BULAN DI WILAYAH PUSKESMAS GODEAN 1 SLEMAN - Alief Nur Insyiroh (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2023)
Introduction: The incidence of toddler stunting is one of the nutritional problems experienced by every toddler in the world today. In 2017 22.2% or around 150.8 million toddlers in the world improved stunting. Stunting of stunting toddlers in Indonesia according to Riskesdas data in 2013 amounted to 37.2% or around 9 million under-fives. In the preliminary study conducted in December in the work area of ​​Godean Health Center 1 under-fives unemployed in 20 large cases and 263 short stunting. SDIDTK's target for toddlers in 2017 was 1767 toddlers, while developmental cases in toddlers in the Primary Health Care area in 2016 were 31 cases, increasing in 2017 by 16 cases, and in 2018 being 4 cases. Objective: To determine the relationship of growth with motor development in infants aged 24-59 months. Method: The study in this study was cross sectional. The sample used in this study was toddlers aged 24-59 months, with a total sample of 106 toddlers obtained by taking a sample of simple random sampling, bivariate analysis using the Chi square test. Results: There was a relationship between short growth and fine motor development at the age of 24-59 months with OR 4,826. In the Bivariate analysis between the stunting variables with the only outside variables of education that have a significant relationship with OR 7.744. In the multivariate analysis the most preferred variable is stunting and income. Conclusion : In this study there was a relationship between stunting and the development of delicate mototypes of children aged 24-59 months in the Godean 1 Health Center area of ​​Sleman.